Tổng hợp một số dẫn xuất amit của 3alpha-hydroxy-lup-20(29)-en-23,28-dioic axit chiết từ cây chân chim - Lộc, Trần Văn; Sung, Trần Văn (Vietnam Journal of Chemistry, 2014)
Starting from 3α-hydroxy-lup-20(29)-ene-23,28-dioic acid, isolated with high yield from the plant Schefflera octophylla (Lour.) Harms (Araliaceae), a series of amide esters  and amide  acids have been synthetized. All the synthetized compounds are new. Their structures were determined by the IR, MS and NMR spectroscopic method.